EDITORIAL: Connecting the Pacific dots - David Robie (Asia Pacific Network, 2018)
When University of the South Pacific climate change scientist Elisabeth Holland gave a keynote address at the Second Pacific Climate Change Conference at Te Papa Tongarewa in Wellington, New Zealand, on February 2018, her message was simple but inspiring. In an address advocating ‘connecting the dots’ about the climate challenges facing the globe, and particularly the coral atoll microstates of the Asia-Pacific region, she called for ‘more Pacific research, by the Pacific and for the Pacific’. The 2007 Nobel Peace Prize co-recipient, Professor Holland, director of the University of the South Pacific’s Pacific Centre for Environment and Sustainable Development (PaCE-SD), noted many of the global models drawn from average statistics were not too helpful for the specifics in the Pacific where climate change had already become a daily reality.